2002
DOI: 10.1002/jsfa.1205
|View full text |Cite
|
Sign up to set email alerts
|

Respiration rate, ethylene production and biochemical changes during fruit development and maturation of jujube (Ziziphus mauritiana Lamk)

Abstract: Jujube fruits (Ziziphus mauritiana Lamk) of cv Zaytoni were harvested from fruit set until maturity to study some physiological and biochemical changes. Jujube fruit cv Zaytoni displayed a double-sigmoid growth curve with a very short second stage (2 weeks). Changes in respiration rate and ethylene production during fruit development were typical of climacteric fruits, the peak of ethylene production coinciding with the climacteric rise in respiration. As for chemical constituents, reducing sugars were dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 8 publications
1
30
1
Order By: Relevance
“…Jujube fruit showed double sigmoid growth (Bal and Singh, 1978;Abbas and Fandi, 2002). On the basis of diameter and weight, it has been confirmed that jujube fruit having double sigmoid growth from 40 to 88 days after petal fall (Lu et al, 2012).…”
Section: Fruit Growth and Developmentmentioning
confidence: 74%
See 2 more Smart Citations
“…Jujube fruit showed double sigmoid growth (Bal and Singh, 1978;Abbas and Fandi, 2002). On the basis of diameter and weight, it has been confirmed that jujube fruit having double sigmoid growth from 40 to 88 days after petal fall (Lu et al, 2012).…”
Section: Fruit Growth and Developmentmentioning
confidence: 74%
“…On the basis of diameter and weight, it has been confirmed that jujube fruit having double sigmoid growth from 40 to 88 days after petal fall (Lu et al, 2012). Cultivar differences were found for days taken to maturity e.g., 'Changhong' Jujube fruit matures in 80 days (Lu et al, 2011), whereas 'Zaytoni' took 124 days (Abbas and Fandi, 2002). Due to the rapid cell elongation and cell division (Bollard, 1970) as well as high levels of growth hormons particularly auxins, gibberellins, and cytokinins (Fandi, 1999) the first rapid growth was observed between 40 to 48 days after petal fall (Lu et al, 2012).…”
Section: Fruit Growth and Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…The TA was decreasing due to increase of soluble sugars during the course of ripening (Abbas and Fandi, 2002). This decrease was observed less in treated ones as compared to control as they have less TSS due to edible coating.…”
Section: Titrable Aciditymentioning
confidence: 88%
“…This trend was continued in the aloe-pectin treated fruits during 20 days of storage (Fig.6). The total soluble solids increases in all the fruits as the fruit ripens (Abbas and Fandi, 2002) the complex carbohydrates were converted to simple sugars. But this increase could be prevented to some extent with the help of aloe-pectin edible coating (Valverde et al, 2005).The mean of the treatments shows that total soluble solids was maintained better in ST6 and ST7 and less deviated from the standard when compared to other treatments.…”
Section: Chemical Parameters Of Sapota Qualitymentioning
confidence: 99%